Two-photon absorption properties of fluorescent proteins - Drobizhev, Mikhail (Nat Methods, 2011)
Two-photon excitation of fluorescent proteins is an attractive approach for imaging living systems. Today researchers are eager to know which proteins are the brightest, and what the best excitation wavelengths are. Here we review the two-photon absorption properties of a wide variety of fluorescent proteins, including new far-red variants, to produce a comprehensive guide to choosing the right FP and excitation wavelength for two-photon applications.